Does the Political Resource Curse Affect Public Finance? The Vulnerability of Tax Revenue in Resource‐Dependent Countries. (13th March 2018) - von Haldenwang, Christian; Ivanyna, Maksym
Abstract: This paper explores the extent to which government revenue is affected by external shocks and whether these effects are different for resource‐dependent (RD) as compared with non‐RD countries. We are particularly interested in the fate of poorer countries, as we assume they will find it more difficult to implement the policies needed to offset the effect of shocks. Based on data from the International Centre for Taxation and Development Government Revenue Dataset for 1980–2010, we measure the elasticity of tax revenue with respect to terms‐of‐trade shocks. We find that revenue in RD countries is more vulnerable to such shocks. It is above all the richer countries that appear to be adversely affected, compared with their non‐RD counterparts. In contrast, the difference between RD and non‐RD countries is less pronounced in the group of poorer countries. We also find that resource‐dependent countries became less vulnerable in the 2000s as compared with previous decades. At the same time, political regime type does not seem to matter for the vulnerability of government revenue in these countries. © 2018 UNU‐WIDER. Journal of International Development published by JohnWiley & Sons, Ltd